2019
DOI: 10.1103/physrevd.100.095020
|View full text |Cite
|
Sign up to set email alerts
|

Probing light dark matter with a hadrophilic scalar mediator

Abstract: We investigate the thermal cosmology and terrestrial and astrophysical phenomenology of a sub-GeV hadrophilic dark sector. The specific construction explored in this work features a Dirac fermion dark matter candidate interacting with a light scalar mediator that dominantly couples to the up-quark. The correct freeze-out relic abundance may be achieved via dark matter annihilation directly to hadrons or through secluded annihilation to scalar mediators. A rich and distinctive phenomenology is present in this s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 144 publications
1
90
0
Order By: Relevance
“…While DM is less likely to be mainly composed of astrophysical objects [24][25][26][27][28][29][30][31][32][33][34], there are no particle physics candidates in the standard model (SM), and many models beyond it are under investigation [1,3,4,. The "weakly interacting massive particles miracle" [41,[86][87][88][89][90][91][92][93][94], i.e., the suggestive coincidence of the weak coupling and the DM density that would have thermally been generated with the latter as the interaction between ordinary matter and DM, motivated us to experimentally test their direct scattering [95][96][97][98][99][100][101][102][103][104][105][106][107][108][109], the DM decay to visible cosmic rays , and DM productions at collider experiments [98,, but no positive results have been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…While DM is less likely to be mainly composed of astrophysical objects [24][25][26][27][28][29][30][31][32][33][34], there are no particle physics candidates in the standard model (SM), and many models beyond it are under investigation [1,3,4,. The "weakly interacting massive particles miracle" [41,[86][87][88][89][90][91][92][93][94], i.e., the suggestive coincidence of the weak coupling and the DM density that would have thermally been generated with the latter as the interaction between ordinary matter and DM, motivated us to experimentally test their direct scattering [95][96][97][98][99][100][101][102][103][104][105][106][107][108][109], the DM decay to visible cosmic rays , and DM productions at collider experiments [98,, but no positive results have been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming the above estimates of the loop-induced couplings, we find however that the rates for energy transfer 2 A recent study showed the importance of the thermal mass for DM production from thermal photon decays [41]. 3 A similar model was considered in [43] and flavor issues in this class of models were addressed in [44,45].…”
Section: Simplified Dark Matter Modelmentioning
confidence: 94%
“…For example, see Refs. [67,121] for a scalar which couples to top quarks only or up quarks only. Ref.…”
Section: Scalar Mediator Portalsmentioning
confidence: 99%
“…The result for the lowest masses was achieved using a 0.5 g sapphirecrystal (Al 2 O 3 ) with a threshold of 20 eV. The cryogenic crystal was operated above ground without significant shielding for 2.27 hours, the background level in the region of interest was 1.2 ⇥ 10 5 events/(kg ⇥ d ⇥ keV ee ) [121]. In a small window around 0.5-06 GeV/c 2 the best exclusion limit around 3 ⇥ 10 37 cm 2 is from NEWS-G, a spherical proportional counter with 60 cm diameter and filled with a Ne+CH 4 (0.7%) gas-mixture at 3.1 bar (corresponding to 283 g) [122].…”
Section: Scattering Rates and Experimental Statusmentioning
confidence: 99%